Project Innovative Activity in the Higher Education System of the Russian Federation - D. Y. Mironova; E. A. Pashkova; I. V. Baranov; A. G. Budrin; V. Varadarajan; S. Afrifa (Высшее образование в России)
A serious transformation of methods for implementing innovative activities, which is happening today in Russia, is difficult without improvement of the processes for managing project innovation activities of universities. This issue is not widely studied in the scientific community despite its relevance and significance. The purpose of this work is to study the theoretical foundations of project innovation activities of universities in the Russian Federation, as well as to analyze the demand for project innovation activities of domestic universities. The work presents a map of concepts in the innovation sphere, which depicts the relationship between such concepts as: innovation, project, innovation activity, project activity, innovation infrastructure, design-innovation activity, innovative developments and innovative project. The paper examines key problems and trends in project innovation activities of universities in the Russian Federation, as well as the factors without which successful implementation of this activity can’t be possible. Owing to the current study, it is obvious that the development of a new approach to innovation activities project management in universities is required, taking into account current trends in the country’s socio-economic development and the geopolitical situation.